2020
DOI: 10.1016/j.bbih.2020.100060
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide animal models of Parkinson’s disease: Recent progress and relevance to clinical disease

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative movement disorders which is characterised neuropathologically by progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and the presence of Lewy bodies (made predominately of α-synuclein) in the surviving neurons. Animal models of PD have improved our understanding of the disease and have played a critical role in the development of neuroprotective agents. Neuroinflammation has been strongly implicated in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 115 publications
3
82
0
Order By: Relevance
“…The only report comparing both models uses an indirect approach, studying the LPS-induced neuroin ammation in the SNpc after a striatal injection [29]. This is actually the most adequate approach for a PD-like in ammatory reaction since injecting into the striatum avoids the direct damage caused by LPS in the SNpc but generates an indirect microglial activation while structurally preserving the area of interest [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only report comparing both models uses an indirect approach, studying the LPS-induced neuroin ammation in the SNpc after a striatal injection [29]. This is actually the most adequate approach for a PD-like in ammatory reaction since injecting into the striatum avoids the direct damage caused by LPS in the SNpc but generates an indirect microglial activation while structurally preserving the area of interest [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that intranigral LPS injection generates reliable neuronal loss, which can be suitable for particular scienti c questions [6], but whether the in ammation of this model is comparable to PD-like in ammation is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPS-treated mice has been extensively used as a PD model, since various observations revealed that LPS may induce the progressive loss of dopaminergic neurons and motor impairments analogous to the clinical symptoms of PD in humans, which are often correlated with immune dysregulation and the inherent molecular and cellular mechanisms [ 159 , 160 ]. Oral administration of purple sweet potato colors, seen as stable anthocyanins, seemed to be effective in improving the motor disabilities in LPS-treated mice.…”
Section: Anti-neuroinflammatory Activity Of Anthocyanins and Theirmentioning
confidence: 99%